Zoledronic Acid in Osteoporotic Vertebral Compression Fractures Treated With Percutaneous Kyphoplasty: A Meta-Analysis - Tian, Peng (Front Surg, 2021)
Background: We performed a meta-analysis to evaluate the efficacy and safety of zoledronic acid combined with percutaneous kyphoplasty (PKP) in treating osteoporotic vertebral compression fractures (OVCFs). Methods: Eligible scientific articles published prior to July 2020 were retrieved from the PubMed, Springer, ScienceDirect, and Cochrane Library databases. The statistical analysis was performed with RevMan 5.1. Results: Three randomized controlled trials (RCTs) and 2 non-RCTs met the inclusion criteria. The present meta-analysis revealed that zoledronic acid combined with PKP is associated with a higher BMD, a better quality of life, less severe low back pain, and fewer additional vertebral body fractures than is percutaneous vertebral augmentation alone. Conclusions: Compared with PKP only, zoledronic acid combined with percutaneous vertebral augmentation is beneficial for OVCFs.